Memberdayakan Kewirausahaan Sosial: Peran Pengalaman Kerja Sosial, Dukungan Universitas, Empati, dan Efikasi Diri dalam Membentuk Niat Berwirausaha - Rahmayanti, Putu Laksmita Dewi; Purba, Ida Ayu Putri Laksmidewi; Juliartini, Ketut; Buditama, Wayan Satya Pariana (Jurnal Bisnis dan Kewirausahaan, 2025)
Social entrepreneurship provides innovative approaches to addressing social challenges; however, students’ willingness to pursue this path remains relatively low. This study investigates the impact of social work experience and university-based entrepreneurial support on students’ social entrepreneurship intention, with empathy and self-efficacy serving as mediating variables. Employing a quantitative method, the study involved 230 student respondents and utilized Partial Least Squares-Structural Equation Modeling (PLS-SEM) through SmartPLS 3.0 for data analysis. The findings reveal that both empathy and self-efficacy have a significant positive effect on students’ intention to engage in social entrepreneurship. Moreover, social work experience was found to enhance empathy, while university support contributed to strengthening students’ self-efficacy. These results highlight the critical role of meaningful social engagement and a supportive academic environment in fostering social entrepreneurial intentions. The practical implication suggests that higher education institutions should integrate entrepreneurship education with hands-on social involvement within their curricula.